Rehabilitacija odraslih oseb po zmerni in težki možganski poškodbi - Grabljevec, Klemen (Zdravniški vestnik, 2015)
Traumatic brain injury is any non-degenerative and non-congenital injury of the brain and the surrounding tissue caused by an external mechanical force. Its short- and long-term consequences on cognitive, behavioral and physical functioning are not limited to injury itself but are closely connected with the secondary cellular metabolic and vascular changes after the acute impact. High mortality, extremelly demanding acute treatment, long term need for intensive rehabilitation and inevitably permanent deficits on subject%s multi-level functioning, render severe traumatic brain injuries the most acute medicosocial problem of the developed world. There are many different national guidelines available in the literature for rehabilitation of subjects after traumatic brain injury. A protocol for early recognition and prevention of complications after and during admission in the rehabilitation programme serves as a protection against events that too often prevent an effective progress in rehabilitation, entail serious long-term consequenses for the patient and cause additional costs of medical care. The Slovenian guidelines for rehabilitation after moderate / severe traumatic brain injury in acute and post-acute phase are presented.
Keywords: Brain injuries; complications; Guidelines as Topic; poškodbe možganov; rehabilitacija; rehabilitation; smernice; vocational rehabilitation; zapleti